Elevated serum apelin levels in breast cancer patients: A potential biomarker with limited histopathological correlations - Soltanizadeh, Adel; Tirgar, Aliasghar; Zamanian, Yasaman; Ilaghi, Mehran; Aflatoonian, Sarah; Karamoozian, Ali; Shabani, Mohammad; Jafari, Elham; Mahmoudabadi, Ali; Moazed, Vahid (Frontiers in Oncology, 2025)
BackgroundApelin, a peptide implicated in various physiological processes, has been shown to be involved in cancer development and progression. However, its role in breast cancer remains unclear. This study aimed to investigate serum apelin levels in breast cancer patients and explore potential associations with clinicopathological features.MethodsThis study involved 137 histopathologically-confirmed female breast cancer patients and 71 healthy controls. Serum apelin levels were measured using enzyme-linked immunosorbent assay (ELISA) and patients’ clinicopathological data was collected retrospectively. Serum apelin levels were compared between the patients and control groups. Moreover, Youden’s J index and the receiver operating characteristic (ROC) curve analysis were utilized to select the optimal cut-off point to differentiate patients and healthy controls. A generalized linear model (GLM) was used to investigate the association of each histopathological variable with serum apelin levels.ResultsSerum apelin levels were significantly higher in breast cancer patients (343.61 ± 182.69 pg/mL) compared to healthy controls (67.37 ± 30.18 pg/mL, p<0.001). ROC curve analysis revealed excellent discriminative ability of serum apelin in distinguishing breast cancer patients from healthy controls (AUC = 0.94, 95% CI: 0.91-0.98). The optimal cut-off value for serum apelin was determined to be 122.48 pg/mL, yielding 89% sensitivity and 97% specificity. However, GLM analysis found no statistically significant associations between serum apelin levels and clinicopathological features, including age, tumor size, histologic grade, lymphovascular invasion, lymph node involvement, microcalcification, in situ components, necrosis, Ki67 expression, molecular subtypes, and clinical stage.ConclusionsOur findings suggest a potential role for serum apelin in breast cancer pathogenesis or progression. The high discriminative ability of serum apelin indicates its promise as a biomarker for breast cancer detection. However, the lack of association between serum apelin levels and specific clinicopathological features suggests a limited prognostic value and a complex role in breast cancer biology that warrants further investigation.